2014
DOI: 10.7498/aps.63.224203
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic generation and manipulaition of electromagnetically induced 2D phtonic band-gaps

Abstract: We study the steady optical responses of a four-level Tripod cold 87Rb atomic system, which is driven by two mutually perpendicular strong standing-wave laser fields. It is found that satisfying the condition of a proper detuning between two strong fields, one nearly perfect structure of double photonic band-gap, where reflectivity can reach 95%, can be generated along each direction, respectively. Shifting a strong field (two strong fields) to a travelling-wave field (two travelling-wave fields), we can achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…So, people have proposed the use of electromagnetically induced transparency (EIT) [4] to obtain tunable PBG in cold atoms driven by a standing-wave field. [5][6][7][8] It is important to note that the spatially periodic coherent effect can be generated in cold atoms confined in an optical lattice. [9][10][11][12][13][14] In a theoretical paper, Petrosyan showed that such a system could induce a new PBG under the condition of EIT.…”
Section: Introductionmentioning
confidence: 99%
“…So, people have proposed the use of electromagnetically induced transparency (EIT) [4] to obtain tunable PBG in cold atoms driven by a standing-wave field. [5][6][7][8] It is important to note that the spatially periodic coherent effect can be generated in cold atoms confined in an optical lattice. [9][10][11][12][13][14] In a theoretical paper, Petrosyan showed that such a system could induce a new PBG under the condition of EIT.…”
Section: Introductionmentioning
confidence: 99%